2011
DOI: 10.1111/j.1365-2354.2011.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

A UK collaborative 1-day pilot information and support forum facilitated by a national breast cancer charity and NHS cancer genetic counsellors, for women at high risk, BRCA 1/2 gene carriers and hereditary breast cancer

Abstract: Since the identification of the breast cancer susceptibility genes BRCA 1/2, genetic assessments of individuals and their families has greatly increased. The assessment of an individual as being at high risk, a gene carrier or an inheritor of cancer changes that individual's life. There is then a great need for ongoing information and support, not only from healthcare professionals but from peers - other women in the same situation. Breast Cancer Care is aware of this need; for a number of years, we have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Five publications described one-day interventions: these ranged from more casual retreats to more structured information sessions to a conference with seminars, teleconferences, and webinars. Discussion topics included general information about hereditary breast and ovarian cancers, risk-reducing surgeries and surveillance, and body image and sexual health [ 16 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five publications described one-day interventions: these ranged from more casual retreats to more structured information sessions to a conference with seminars, teleconferences, and webinars. Discussion topics included general information about hereditary breast and ovarian cancers, risk-reducing surgeries and surveillance, and body image and sexual health [ 16 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported a decrease in anxiety and psychological distress, and one study observed no significant change [ 32 , 33 , 34 ]. Participants in one-day sessions reported feeling less isolated, more empowered, and reported high satisfaction with the intervention [ 16 , 33 , 35 ]. McKinnon et al found half of their participants that altered their health behaviour did so as a result of the intervention; this included increasing cancer screening and completing or considering surgery [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…143,153 Genetic counsellors provide significant levels of long-term psychosocial support to patients and their families, termed "support counselling". 154 This allows genetic counsellors to help the patients cope with the test data.…”
Section: Familial Cancer Genetic Counselling Clinic In Saudi Arabiamentioning
confidence: 99%
“…Nevertheless, despite the clinical relevance of such meetings, several additional needs have been expressed, such as the need for information about the surgery and follow-up care, as well as the desire to speak to a woman who had undergone prophylactic mastectomy (Dorval et al 2013;Farrelly et al 2012;McQuirter et al 2010;Patenaude et al 2008;Wasteson et al 2011;Werner-Lin 2008). In several centers, some initiatives have been proposed to enable women to access peer support through discussions with other women who have undergone similar procedures (Harris and Ward 2011;Leff et al 2015). However, our understanding remains limited.…”
Section: Introductionmentioning
confidence: 99%